2011
DOI: 10.3233/jad-2010-101377
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Perspective for Alzheimer's Disease: Vitamin D Receptor Suppression by Amyloid-β and Preventing the Amyloid-β Induced Alterations by Vitamin D in Cortical Neurons

Abstract: Amyloid-β (Aβ) is the core component of amyloid plaques of Alzheimer's disease (AD). The effects of Aβ include damage to neuronal plasma membrane, disruption of Ca(2+) homeostasis, and alterations of neurotrophic factor levels. The aim of this study was to determine the effects of Aβ treatment on vitamin D receptor (VDR), L-type voltage sensitive calcium channels A1C (LVSCC A1C), NGF, and observing the effects of vitamin D treatment on Aβ induced alterations in primary cortical neurons. As to the latter, we ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(156 citation statements)
references
References 0 publications
6
141
0
9
Order By: Relevance
“…In cell based experiments, vitamin D has been shown to inhibit Aβ induced cytotoxicity and apoptosis in cultured cortical neurons [183]. In post-mortem AD brain, a decreased level of VDR mRNA has been reported in hippocampal region [184].…”
Section: Vitamin Dmentioning
confidence: 99%
“…In cell based experiments, vitamin D has been shown to inhibit Aβ induced cytotoxicity and apoptosis in cultured cortical neurons [183]. In post-mortem AD brain, a decreased level of VDR mRNA has been reported in hippocampal region [184].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Vitamin D may have neuroprotective properties by decreasing inflammation and oxidative stress (1,2). Vitamin D receptors have been shown to be present in brain regions that are responsible for memory development and cognitive functions (3,4) and may also be involved in plaque clearance (5,6). Vitamin D is produced in the skin by UVB sunlight, and a smaller amount of vitamin D is provided by the diet.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of studies, it has been indicated that vitamin D in the brain regulates neurotrophic factor expression, oxidative stress mechanisms and Ca 2+ homeostasis (25)(26)(27)(28)(29)(30)(31). Vitamin D may affect neuronal plasticity processes and increase neurite outgrowth when added to cultured hippocampal cells (28).…”
Section: Discussionmentioning
confidence: 99%